Perbedaan gender dalam pembelajaran matematika: studi kesalahan pemecahan masalah berdasarkan Newmann Error Analysis - Putri, Maulia; Andriani, Parhaini (Jurnal of Math Tadris, 2023)
Abstract Students’ errors in solving mathematics problems, especially  in word problems, are influenced by various factors. One aspect to consider is gender differences. This study aims to describe the types of student errors in solving mathematics word problems on the topic of fractions based on gender. This study is qualitative research with a case study type. This research involved 2 male and 2 female students of class VII MTs. NW Bagik Polak, West Lombok. The instruments used were non-routine tests, rubrics for assessing errors and interview guidelines. The data obtained were analyzed using Newman Error Analysis (NEA). This study found that male and female students made almost the same types of errors. However, female students still found reading errors, while male students did not. These findings can be used as a reference for teachers in designing learning and providing assistance to students who have difficulty solving math problems.